COMPARISON OF ANESHTETIC EFFICACY OF INFERIOR ALVEOLAR NERVE BLOCK AND VAZIRANI-AKINOSI TECHNIQUES IN PATIENTS WITH IRREVERSIBLE PULPITIS - Shah, Fawad Ali; Jan, Inam Ullah; Ali, Ahsan; Afridi, Rizwan Ullah; Zain, Muhammad; Haider, Sulman (Pakistan Oral & Dental Journal, 2019)
Successful anesthesia is the bedrock for pain control in dentistry. It not only reduces the stress of the dentist but also raises patient comfort, affiliation and faith in the operator. Inferior alveolar nerve block is commonly used to anesthetize mandibular posterior teeth. However, anesthetizing teeth with irreversible pulpitis is still challenging for a dentist. The aim of the study was to compare two anesthetic techniques, i.e., Inferior alveolar nerve block to Vazirani-Akinosi technique in patients presenting with irreversible pulpitis. A retrospective randomized controlled trial was conducted at department of operative dentistry, Khyber College of Dentistry, Peshawar, from March 2018 to August 2018. A total of 80 patients having irreversible pulpitis in posterior mandibular teeth were selected. They were divided randomly (lottery method) in to two groups of 40 patients each. Each group of subjects received 2% lidocaine of 1.8mL with epinephrine 1: 100,000 (Medicainer Inj, Huon Co.,Ltd, Korea) using anesthetic cartridges with aspirating syringe. Group A subjects received inferior alveolar nerve block while Group B subjects received Vazirani-Akinosi nerve block. Each patient had rated his or her pre-operative and intra-operative pain on a visual analog scale (VAS). Data was analyzed using SPSS-22. Efficacy between both the groups were compared. Efficacy was observed in 30 patients (75%) of Group-A and 38 patients (95%) of Group-B. In conclusion, the success rate of Vazirani-Akinosi technique and inferior alveolar nerve block differs considerably. Varizani-Akinosi technique may be consider as a suitable alternative to the Inferior alveolar nerve block technique in anesthetizing patients with irreversible pulpitis having anesthetic success of (95%) as compared to Inferior alveolar nerve block (75%).